2013
DOI: 10.3109/02656736.2013.825014
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic nanoparticle hyperthermia enhancement of cisplatin chemotherapy cancer treatment

Abstract: Purpose The purpose of this study was to examine the therapeutic effect of magnetic nanoparticle hyperthermia (mNPH) combined with systemic cisplatin chemotherapy in a murine mammary adenocarcinoma model (MTGB). Materials and methods An alternating magnetic field (35.8 kA/m at 165 kHz) was used to activate 110 nm hydroxyethyl starch-coated magnetic nanoparticles (mNP) to a thermal dose of 60 min at 43 °C. Intratumoral mNP were delivered at 7.5 mg of Fe/cm3 of tumour (four equal tumour quadrants). Intraperito… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
53
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 67 publications
(56 citation statements)
references
References 19 publications
2
53
0
1
Order By: Relevance
“…When the tumor volume reached approximately 100 mm 3 , the mice were divided into control (n =2 ), MHT (n =2 ), CDDP (n =2 ), and MHT+CDDP groups (n =2 ). In the control group, the mice were sacrificed and the tumors were removed 3 days after the tumor volume exceeded 100 mm 3 . In the MHT and MHT+CDDP groups, the mice were sacrificed and the tumors were removed 3 days after MHT.…”
Section: Histological Studymentioning
confidence: 99%
See 4 more Smart Citations
“…When the tumor volume reached approximately 100 mm 3 , the mice were divided into control (n =2 ), MHT (n =2 ), CDDP (n =2 ), and MHT+CDDP groups (n =2 ). In the control group, the mice were sacrificed and the tumors were removed 3 days after the tumor volume exceeded 100 mm 3 . In the MHT and MHT+CDDP groups, the mice were sacrificed and the tumors were removed 3 days after MHT.…”
Section: Histological Studymentioning
confidence: 99%
“…Thus, the above conditions for the AMF, duration of MHT, and injection dose of Resovist ® appear to have been appropriate for the purpose of this study. Petryk et al reported that intraperitoneal administration of CDDP at a dose of 5 mg/kg body weight improved the delivery of MNPs to tumors in C3H mice inoculated intradermally with MTG-B cells 5) and it helped to enhance the therapeutic effect of MHT 3) . Thus, we also injected CDDP into mice intraperitoneally at a single dose of 5 mg/kg body weight according to their protocol.…”
Section: Therapeutic Effectmentioning
confidence: 99%
See 3 more Smart Citations